Architecting Silk Protein and Melanin for Photoresponsive and Self-Healable Optoelectronic Skins - Wahab, Abdul; Gogurla, Narendar; Park, Ji Yong; Kim, Sunghwan (Advanced Materials Technologies, 2022)
The central processes driving biological phenomena are based on the conduction of ions and electrons in biomaterials, implying the possibility of achieving a fully biomaterial-based electronic skin. However, finding the appropriate biomaterials for electronic skins is still challenging. Here, a photoresponsive, self-healable, and biomaterial-based optoelectronic skin (OE-skin) fabricated with melanin nanoparticles and silk protein is proposed and the electronic properties and their mechanisms in the artificially generated OE-skin are reported. Not only does silk protein hydrogel provide a transparent and skin-compatible platform for use as OE-skin but it also provides the appropriate environment for melanin to demonstrate high electrical conductivity. The OE-skin can be considered a p-type semiconducting material showing high conductivity of up to 6 mS cm−1 in addition to a 40% enhancement in the conductivity by green laser and ultraviolet light emitting diode illuminations. Additionally, the OE-skin autonomously heals itself from multiple cuts, allowing the restoration of its electrical properties. These material properties enable applications for strain-sensors, humidity sensors, and ultraviolet light sensors, as well as image pixels to convert light-lettering into electrical signals. The proposed fully biomaterial-based OE material platform offers a new way for next-generation electronic skins to achieve a seamless interface with the human body.
Keywords: Biological phenomena; Electronic skin; High conductivity; High electrical conductivity; P-type; Photo-responsive; Protein hydrogels; Self-healable optoelectronic skin; Semiconducting materials; Silk proteins; melanin; self-healable optoelectronic skin; silk protein